The Role of Faith-Based Organizations in HIV Prevention and Care in Central America (Spanish translation) - Derose, Kathryn Pitkin (RAND Corporation, 2010)
Describes the involvement of churches and other faith-based organizations (FBOs) in addressing the HIV/AIDS epidemic in Belize, Guatemala, and Honduras. The authors describe the range of FBO activities and discuss the advantages and challenges to such involvement and possible ways that FBOs can enhance their efforts, both independently and in collaboration with other organizations, such as government ministries of health.